DETERMINING THE STRENGTH OF THE CEMENT-CARRYING WAGON-HOPPER AGAINST OVERTURNING (American Journal of Pedagogical and Educational Research, 2023)
The purpose of the study is to check the stability calculation of the cement-carrying wagon-hopper against overturning. Research work was carried out based on "Standards for calculation and design of new and modernized wagons, 1520 mm gauge (non-self-propelled) norms of the Ministry of Railways". According to the requirement, the calculations were performed based on two calculation cases: because of rolling off the curve and based on rolling on the curve. As a result, in the case of the first calculation, the car has a reserve of stability in case of overturning out of the curve. In the case of the second calculation, it was found that the wagon has a reserve of stability when it rolls into a curve. According to the calculation results, the 19-9596 model hopper wagon for cement transportation meets regulatory requirements for rollover resistance.